2017
DOI: 10.1111/pace.13186
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the vanishing PVC, facilitated by quantitative morphology‐matching software

Abstract: (1) Spontaneous VA frequency was markedly reduced following anesthesia, despite catecholamine administration. (2) Notwithstanding the ability to perform AT mapping, successful ablation can still be performed using pace mapping only, facilitated by the PaSo software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…More recently, Fedida et al used the proprietary software PASO to perform quantitative template matching from various PVC locations and demonstrated that the median distance between the earliest activation sites and the highest pace‐mapping correlation sites was 6.4 mm. One smaller study of pediatric patients demonstrated comparable success rates between those ablated with activation mapping and those with pace‐mapping only …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fedida et al used the proprietary software PASO to perform quantitative template matching from various PVC locations and demonstrated that the median distance between the earliest activation sites and the highest pace‐mapping correlation sites was 6.4 mm. One smaller study of pediatric patients demonstrated comparable success rates between those ablated with activation mapping and those with pace‐mapping only …”
Section: Discussionmentioning
confidence: 99%
“…The similarity of surface electrocardiography between paced beat and spontaneous ventricular ectopy suggest that catheter tip is near the origin of ventricular ectopy. Quantitative comparison of paced beat and spontaneous ventricular ectopy can assist catheter ablation …”
Section: Chapter 2: Principles Of 3d Mappingmentioning
confidence: 99%
“…At successful ablation sites, earliest activation on the bipolar local electrogram usually precedes the earliest QRS onset by 15‐45 milliseconds during the PVC . One of the big obstacles of OT‐PVC ablation is that often times the patient only displays very few PVC at the time of the study, a problem that is compounded in patients undergoing this procedure under conscious sedation or general anesthesia, for example in children or adolescents . Frequency of PVC less than 1 PVC/min is associated with a significantly lower success rate .…”
Section: Chapter 10: Idiopathic Outflow Tract Ventricular Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the article entitled ‘Ablation of the Vanishing PVC, Facilitated by Quantitative Morphology‐Matching Software’ by Moak et al. in the latest issue of the journal . They presented their pace mapping experiences in ventricular arrhythmia ablation using PASO™ (Biosense Webster, Diamond Bar, CA, USA) software that compares induced signals (arrhythmia) with pace mapping signals and demonstrates correlations in both 12 individual leads and average of all.…”
mentioning
confidence: 99%